White-Collar Crime Prevention Through Corporate Governance Mechanisms: Evidence from Emerging Markets - Muh Fadli Faisal Rasyid (Proceeding of the International Conference on Law and Human Rights, 2025)
White-collar crime poses significant threats to corporate integrity and economic stability, particularly in emerging markets where governance structures may be less developed. This study examines the effectiveness of corporate governance mechanisms in preventing white-collar crime in emerging market contexts. Using a mixed-methods approach combining quantitative analysis of 240 publicly listed companies across five emerging markets and qualitative case study analysis of 25 corporate fraud cases, this research evaluates the relationship between governance mechanisms and crime prevention effectiveness. The study reveals that strong board independence (β = -0.312, p < 0.001), robust internal audit functions (β = -0.267, p < 0.01), and comprehensive compliance programs (β = -0.298, p < 0.001) significantly reduce white-collar crime incidence. Companies with comprehensive governance frameworks show 58% lower fraud rates compared to those with weak governance structures. The research concludes that emerging markets can significantly reduce white-collar crime through strategic implementation of governance mechanisms, particularly emphasizing board independence, internal controls strengthening, and compliance culture development.